Spectral Characteristics of Narrow Linewidth InAs/InP Quantum Dot Distributed Feedback Lasers - Septon, Tali; Gosh, Sutapa; Becker, Annette; Eyal, Ori; Bjelica, Marco; Sichkovskyi, Vitalii; Rippien, Anna; Schnabel, Florian; Witzigmann, Bernd; Reithmaier, Johann P.; Eisenstein, Gadi (Conference Digest - IEEE International Semiconductor Laser Conference, 2018)
We report spectral characteristics of InAs/InP QD DFB lasers. Owing to low linewidth enhancement factor and high modal gain, lasers with 5 QD layers exhibit record linewidth of 55 kHz measured by the heterodyne beat note between the laser and an ultra-stable optical frequency comb.
CRIS-Team Scopus Importer:2021-06-11